Assessing the Impact of Internal Control, Accounting Systems, and Organizational Commitment on Financial Accountability through Financial Information Quality - Megawati, Megawati; Suyuthi, Nurmadhani Fitri; Hasniaty, Hasniaty (Journal of Management and Administration Provision, 2023)
This study investigates the influence of internal control, accounting systems, and organizational commitment on financial management accountability through the quality of financial information at the Penajajam Paser Utara District KPU Office. The research is motivated by the importance of accountability in the context of election organizing bodies, particularly in Indonesia, where elections play a crucial role in democratic processes. Using a quantitative approach, data was collected from the North Penajam Paser Regency General Election Commission Office. The results indicate that internal control and the accounting system do not significantly affect the quality of financial information. However, organizational commitment demonstrates a significant influence on financial information quality. Furthermore, financial management accountability is significantly influenced by both the quality of financial information and internal control, but not by the accounting system or organizational commitment. These findings underscore the importance of organizational commitment and internal control in ensuring financial management accountability in election commissions.